PEMBELAJARAN MENULIS KARYA TULIS ILMIAH DENGAN METODE DISCOVERY DI PERGURUAN TINGGI - Marya Ulfa (Jurnal CULTURE (Culture, Language, and Literature Review), 2021)
This research is entitled "Learning to Write Scientific Papers with the Discovery Method in Higher Education". The problem in this research is how to learn scientific writing with the discovery method in universities? The purpose of this research is to describe the learning of scientific writing with the discovery method in universities. The method used in this research is descriptive qualitative. Based on the results of the study, the discovery method has not been widely applied by lecturers in learning scientific writing. The obstacles are 1) lecturers still use the assignment method and examples, 2) lecturers still have difficulty in compiling learning tools using the discovery method, and 3) lecturers only provide scientific writing material due to a systematic misunderstanding between general and environmental rules. Therefore, scientific writing material needs to be given to students based on the discovery method. The selection of the right learning method is very influential on the success of students in scientific writing. The facts obtained indicate the need for appropriate learning methods.